The increasing risk of temporomandibular disorder and articular eminence inclination due to tooth loss - Chairunnisa, Ricca; Harahap, Rahmadhani (Universitas Padjadjaran, 2022)
ABSTRACTIntroduction: Tooth loss leads to increased biomechanical pressure in the temporomandibular joint due to changes in the functional movement pattern of the jaw, resulting in joint structure damage specifically change of the articular eminence inclination (AEI) angle, which is one of the increased risks of the temporomandibular disorder (TMD). This study aimed to analyze the relationship between the number and quadrants of tooth loss on TMD and the AEI. Methods: It was descriptive-analytic study using a cross sectional design. The study was done in Universitas Sumatera Utara (USU) Dental hospital, conducted questionnaires and panoramic radiographic on 42 subjects aged over 18-64 years with tooth loss. Data analyzed used Chi-square analysis. Results: The prevalence of TMD on the ≥3 tooth loss group by 82.6% and the four-quadrant group by 93.8%. The prevalence of change in the AEI on the ≥3 tooth loss group was 34.8% on the flat right side, while on the left side of 26.1% was flat, and 13% was steep. Based on the number of quadrants tooth loss, the highest was on the four-quadrant group by 50% on flat right side, and on the three-quadrant group was 25% flat, 25% steep on the left side. There was a significant relationship between the number of tooth loss (p=0.023), the number of tooth loss quadrants, and TMD (p=0.016). There was no relationship between the number of tooth loss and the AEI, except for the number of tooth loss quadrants and the AEI on the right side with a significant result (p=0.017). Conclusion: There was relationship between the number of tooth loss, the number of tooth loss quadrants, and TMD and there was no relationship between the number of tooth loss and the AEI, except for the number of tooth loss quadrants and the AEI on the right side.Keywords: Edentulous; tooth loss; temporomandibular disorder; inclination of articular eminence.